Li-ION battery from industrial waste water - Nee, Lim Yong; Ramalingam, Mritha (2021)
The proposed system is an IoT based bus seat occupancy detection system consists of force sensitive sensor. The system able to detect pressure applied on the seat. The needs of manually count number of passengers is eliminated as bus driver able to monitor bus seat occupancy status remotely in visual form.